The Ones Left Unnoticed and the Deceived: The Two Faces of Drama of the Revolutionary Era’s Younger Generation - Проскурина, Елена (Literatūra, 2017)
The article outlines the approaches to understanding the generational drama of “young” authors, whose youth fell on the revolutionary era of the early twentieth century. The work states that The Ones Left Unnoticed was just one of the modi of the revolutionary generation’s dramatic destiny of the early 20th century, relating to the fate of the young, first-wave emigrants. For the young people who stayed in Russia and came to believe in the “affair of the Revolution,” the drama of their destiny manifested itself as the under-lived life: the social and political situation in the country did not give the Revolutionary generation any opportunity to grow old. The motif of under-lived life in all the complexity of its semantic projections was implemented in the works of A. Platonov. The extended position is performed in different genres: the novel (Happy Moscow), drama (The Voice of the Father, The Pupil of Lyceum, Jukebox) and Platonov’s letters. The breadth of the genre space increases the validity of the research position. Involved into the analysis were The Unnoticed Generation by V. Varshavsky, Shipwreck of a Generation by I. Berger and some correlations were made with the life and work of B. Poplavsky. With it, the author came to the conclusion that the two vectors of the Revolutionary generation’s fate – the emigrant (just barely marked by the author) and the Russian domestic – formed a single generational plot with the situation of under-realized/interrupted life in its center. This situation became prophetic for the fate of most of the young Soviet state, the creation of which demanded plenty sacrifices.LIKĘ NEPASTEBĖTI IR APGAUTI: DVI JAUNOS REVOLIUCINĖS KARTOS DRAMOS BRIAUNOSStraipsnyje aptariama „jaunos“ rusų autorių, kurių jaunystė sutapo su revoliucine XX a. pradžios epocha, kartos drama. „Likę nepastebėti“ – tai tik vienas šios dramatiško likimo kartos modusų, susijusių su pirmąja jaunos emigracijos banga. Jaunųjų rusų rašytojų, likusių Rusijoje ir patikėjusių „revoliucijos reikalu“, kartos dramatizmas atsiveria ne tik žvelgiant į jų neišsipildžiusius lūkesčius, bet ir į nenugyventus gyvenimus, ką nulėmė socialinė ir politinė to meto Rusijos situacija, neleidusi tai kartai sulaukti senatvės.Sudėtingi „nenugyvento gyvenimo“ motyvai atsiskleidžia Andrejaus Platonovo kūryboje analizuojant jo skirtingų žanrų kūrinius: romaną („Laiminga Maskva“), dramaturgiją („Tėvo balsas“, „Licėjaus mokinys“, „Ryla“), epistoliką. Platus žanrinis laukas tik patvirtina atlikto tyrimo rezultatus. O tokios knygos, kaip V. Varšavskio „Nepastebėta karta“, J. Bergero „Kartos žlugimas“ ar B. Poplavskio ir V. Itino biografijos, kaip ir jų kūryba, leidžia teigti, kad revoliucinės kartos (emigravusios ir likusios Rusijoje) likimo vektoriai susijungė vieningame bendrame visos kartos siužete, kurio centre – neišsipildžiusio/nutrūkuios gyvenimo situacija. Tokia pati situacija tapo pranašiška ir visos šalies, kūrimosi kelyje pareikalavusios tokių milžiniškų aukų, likimui.
Keywords: V. Varshavsky; “unnoticed generation”; A. Platonov; B. Poplavsky; V. Itin; generational plot; auto document